Modulation of oxygen tension, acidosis, and cell density is crucial for neural differentiation of human induced pluripotent stem cells. (February 2021) - Okada, Rina; Onodera, Kazunari; Ito, Takuji; Doyu, Manabu; Okano, Hirotaka James; Okada, Yohei
Highlights: hiPSCs provide valuable disease models for intractable neurodegenerative diseases. Modulation of microenvironment is crucial for efficient neural differentiation of hiPSCs. Hypoxia did not promote neural differentiation of hiPSCs due to significant cell death in hEBs. Optimization of pH via appropriate CO2 tension improved neural differentiation of hiPSCs. High-cell density culture negatively affected neural differentiation due to acidosis and cell death. Abstract: Human induced pluripotent stem cell (hiPSC)-derived neural cells provide valuable disease models for pathophysiological analysis and drug discovery for intractable neurodegenerative diseases. However, neural differentiation of hiPSCs requires a complex and long culture procedure, which has been a bottleneck for analysis. We previously demonstrated rapid, efficient, and simple motor neuron differentiation from human pluripotent stem cells (hPSCs). Although optimization of the microenvironment for the differentiation of hPSCs has been considered to achieve more efficient differentiation, it has never been investigated in detail. Here, we demonstrated that three microenvironmental modifiers, oxygen (O2 ) tension, pH, and cell density, critically affect neural differentiation of hiPSCs. Hypoxia is known to be involved in neural development in vivo and to promote neural differentiation of PSCs. However, in this study, it caused significant cell death in aggregation culture of human embryoid bodies (hEBs) and negatively affected neural differentiation. Modulation of pH by optimized carbon dioxide (CO2 ) tension improved neural differentiation of hiPSCs, but mild acidosis caused by increased CO2 tension suppressed neural differentiation without cell death. Moreover, high-cell density culture resulted in prominent acidosis and cell death under hypoxic conditions, which synergistically suppressed neural differentiation of hiPSCs. These results suggest that optimization of the microenvironment via O2 tension, pH, and cell density enables more efficient neural differentiation of hiPSCs for the analysis of neurological diseases.